Analisis Fisikokimia dan Organoleptik Enteral berbasis Tepung Kacang Merah dan Sari Apel untuk Penderita Diabetes Melitus - Amelia Filnia Dewi; Afiya Hasna Nabila; Aan Sofyan (Universitas Mohammad Husni Thamrin, 2026)
Nutrition tailored to individual physical conditions is essential to prevent malnutrition. Nutritional intake can be provided enterally using locally available and affordable food sources. This study aimed to analyze the physicochemical and organoleptic characteristics of enteral food made from red bean flour and apple extract using a Completely Randomized Design with three treatments. Results showed viscosity values ranging from 86.75 to 492.65, osmolality from 451 to 532.5, and flow rate from 1.02 to 6.58. Color test values were L (49.8–52.1), A (2.2–3.1), and B (9.3–9.6). Nutrient content met 80–120% of daily requirements. Organoleptic tests identified F1 the most favorable. This combination shows potential as functional dietary alternative for diabetes mellitus therapy.